Reshoring: Does home country matter?. Issue 4 (October 2019) - Wan, Li; Orzes, Guido; Sartor, Marco; Nassimbeni, Guido
Abstract: The role of the country, either home or host, in firms' internationalization has been widely analysed in the International Business field. A large number of studies have shown that home country shapes many aspects of firms' internationalization processes such as investment decisions, location selections, and entry modes. However, these studies mainly focus on the firms' foreign expansion. Little is known about the relations between firms' home country and reshoring processes. This paper aims to analyse whether and how reshoring projects are different across countries, thereby further exploring the underlying home country-related factors contributing to reshoring peculiarities. By using a dataset including 529 cross-industry reshoring projects developed by companies headquartered in five countries (i.e., US, Germany, UK, France, and Italy), the study shows that these projects differ in terms of industry, entry mode, firm size and motivations. Thus, reshoring turns out to be a phenomenon where each country has its own peculiarities. The research further sheds light on the possible institutional, cultural/cognitive and industry/resource-related factors underlying these specificities. This study contributes to both reshoring and international business literature by highlighting how reshoring differs across countries. It also provides policy and managerial implications, at a time when several governments are considering the economic and employment potential of this phenomenon. Highlights: We shed light on the relationship between home country and reshoring, a topic so far neglected in the internationalization literature. The national sub-samples of reshoring projects are compared in terms of industry, entry mode choice, firm size and motivations. The institutional, cultural/cognitive, and industry- and extended resource-based views are adopted. The study shows that reshoring differs across countries.